Wildlife photographer of the year : 50 years - Kidman Cox, Rosamund (Firefly Books Ltd., 2014)
This book showcases the work of 50 years of the BBC's photographic competition, and hundreds of award winners. The exhibition, based at London's Natural History Museum, travels the world and features the work of: Frans Lanting, Jim Brandenburg, David Doubilet, Art Wolfe, Tom Mangelson, Brian Skerry, Paul Nicklen, Anup Shah, and many others.